CHANGING NURSING CARE TIME AS AN EFFECT OF CHANGED CHARACTERISTICS OF THE DIALYSIS POPULATION. Issue 3 (24th March 2020) - de Kleijn, Ria; Uyl‐de Groot, Carin; Hagen, Chris; Franssen, Casper; Schraa, Jeanette; Pasker‐de Jong, Pieternel; ter Wee, Piet
SUMMARY: Background: The population of dialysis patients is ageing. Dialysis nurses are confronted with geriatric patients with multiple comorbidities. Nurses are confronted with an increasing burden of care. Objectives: The present study focused on the question of whether, over time, the increasing age and comorbidities of the haemodialysis population increased nursing care time. Furthermore, we studied potential changes in the predictors of the required nursing time. Design: Observational study. Participants: A total of 980 dialysis patients from 12 dialysis centres were included. Measurements: Nurses filled out the classification tool for each patient and completed a form for reporting patient characteristics for groups of relevant haemodialysis patients at baseline and after 1 and four years. Changes in patient and dialysis characteristics were analysed, as well as the estimated nursing care time needed. Results: An increase in the nursing time needed for dialysis was largely due to decreased mobility, closing of the vascular access and a greater need for psychosocial attention and was most strongly present in incident dialysis patients. The time needed for dialysis decreased as patient participation increased and vascular access changed from catheters to fistulae. Over the four‐year period, the average overall needed nursing care time per haemodialysis session did not change. Conclusions: Our study shows that the average nursing time needed per patient did not change in the four‐year observation period. However, more time is required for incident patients; thus, if a centre has high patient turnover, more nursing care time is needed.